Estrogen-related Receptor Signaling in Skeletal Muscle Fitness - Sopariwala, Danesh; Nguyen, Hao; Narkar, Vihang (International Journal of Sports Medicine, 2023)
Skeletal muscle is a highly plastic tissue that can alter its metabolic and contractile features, as well as regenerative potential in response to exercise and other conditions. Multiple signaling factors including metabolites, kinases, receptors, and transcriptional factors have been studied in the regulation of skeletal muscle plasticity. Recently, estrogen-related receptors (ERRs) have emerged as a critical transcriptional hub in control of skeletal muscle homeostasis. ERRα and ERRγ – the two highly expressed ERR sub-types in the muscle respond to various extracellular cues such as exercise, hypoxia, fasting and dietary factors, in turn regulating gene expression in the skeletal muscle. On the other hand, conditions such as diabetes and muscular dystrophy suppress expression of ERRs in the skeletal muscle, likely contributing to disease progression. We highlight key functions of ERRs in the skeletal muscle including the regulation of fiber type, mitochondrial metabolism, vascularization, and regeneration. We also describe how ERRs are regulated in the skeletal muscle, and their interaction with important muscle regulators (e. g. AMPK and PGCs). Finally, we identify critical gaps in our understanding of ERR signaling in the skeletal muscle, and suggest future areas of investigation to advance ERRs as potential targets for function promoting therapeutics in muscle diseases.
Keywords: nuclear receptors; transcription; exercise; metabolism; angiogenesis; regeneration